Polyamide composition as well as preparation method and application thereof
By developing a polyamide composition containing polyamide resin, glass fiber and specific copolymer, the problem that glass fiber reinforced nylon materials in the prior art are difficult to have high mechanical strength and smooth surface at the same time, and the effect of high adhesion with soft glue and reducing manufacturing cost is achieved.
Patent Information
- Application Number
- CN202411557025.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-11-04
AI Technical Summary
The prior art is difficult to obtain glass fiber reinforced nylon materials with smooth surface while maintaining high mechanical strength, and the cost of modifying soft glue materials is relatively high.
A polyamide composition is developed, including polyamide resin, glass fiber, ethylene-methacrylic-acrylate or ethylene-acrylic-acrylate copolymer, stabilizer and lubricant, prepared by melt blending and side feeding of glass fibers to improve the adhesive properties with soft glue.
The high adhesion between the polyamide composition and the soft glue is achieved, the surface of the material is kept smooth, and the high tensile strength and fluidity are also achieved, reducing the manufacturing cost.
Smart Images

Figure BDA0005116780560000081 
Figure BDA0005116780560000091 
Figure BDA0005116780560000092
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of engineering plastics, and in particular to a polyamide composition and a preparation method and application thereof. Background Art
[0002] Polyamide is the world's first synthetic fiber and is a general term for thermoplastic resins containing repeating amide groups on the main chain of the molecule. Polyamide has excellent mechanical properties and electrical insulation properties, high mechanical strength, good toughness, and excellent heat resistance, weather resistance and friction resistance, so it is widely used in the fields of automobiles, electronics, and consumer electronics. Glass fiber is widely used as a reinforcing filler in nylon materials. A high content of glass fiber can give nylon high strength and high rigidity, but it will also reduce the appearance and surface smoothness of nylon materials. In order to obtain a nylon material with a smooth surface and high mechanical strength, it is currently usually used to bond nylon with different soft glues to improve the skin feel, wear resistance, smoothness and other properties of nylon materials. Commonly used soft glues include TPE, TPU, TPV, etc. In the prior art, in the problem of encapsulation of glass fiber reinforced nylon, a specially modified soft glue material is usually selected to improve the adhesion between the soft glue and nylon, but the cost of special modification of the soft glue material is high. However, current research mainly focuses on soft adhesive alloys, but there is very little research on improving the bonding performance between nylon and soft adhesive by modifying nylon.
[0003] Therefore, in order to obtain glass fiber reinforced nylon materials with high mechanical strength and smooth surface while saving manufacturing costs, it is urgent to develop a nylon composition that has high bonding properties with soft glue, so that the nylon composite material after encapsulation has excellent comprehensive properties. Summary of the invention
[0004] In view of the defects in the prior art, the present invention provides a polyamide composition and a preparation method and application thereof.
[0005] The present invention provides a polyamide composition, which comprises the following components by weight: 40-60 parts of polyamide resin, such as 40, 42, 45, 48, 50, 52, 55, 58, and 60 parts; 2-6 parts of ethylene-methacrylic acid-acrylate or ethylene-acrylic acid-acrylate, such as 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, and 6 parts; 20-40 parts of glass fiber, such as 20, 22, 25, 28, 30, 32, 35, 38, and 40 parts; 0.2-0.5 parts of stabilizer, such as 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5 parts; 1-3 parts of lubricant, such as 1, 1.2, 1.5, 1.8, 2, 2.2, 2.5, 2.8, 3 parts; the mass percentage of methacrylic acid or acrylic acid monomer in the ethylene-methacrylic acid-acrylate or ethylene-acrylic acid-acrylate is 1.8%-9.2%, such as 1.8%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 9.2%; the ethylene content is 55-85%, and the acrylate content is 13-37%; the lubricant is any one of a hyperbranched polyester, a hyperbranched polyamide or a polyethylene lubricant;
[0006] The mass percentage of the polyamide resin in the composition is not less than 40%; the content of methacrylic acid or acrylic acid monomer in the ethylene-methacrylic acid-acrylate or ethylene-acrylic acid-acrylate is obtained by testing methods known in the art, such as by high performance liquid chromatography (HPLC).
[0007] Methacrylic acid or acrylic acid monomers can react with ether bonds or ester bonds in polyether-type and polyester-type TPE materials, thereby improving the compatibility of the polyamide composition with the TPE material; when the methacrylic acid or acrylic acid monomer is greater than 9.2%, the stability of the polyamide composition deteriorates and the overall performance of the polymer decreases; when the methacrylic acid or acrylic acid monomer is less than <1.8%, the reaction sites between the copolymer and TPE are reduced, causing the compatibility of the polyamide composition with TPE to deteriorate.
[0008] The ethylene-methacrylic acid-acrylate or ethylene-acrylic acid-acrylate copolymer of the present invention can be prepared by a polymerization method known in the art, or can be obtained from a commercial source; a self-preparation method is exemplarily provided below, comprising the following steps: uniformly mixing an initiator, water, tert-butyl alcohol (the mass ratio of pure water to tert-butyl alcohol is (4-6):3:1), methacrylic acid or acrylic acid and acrylate in a reaction device, introducing ethylene into the reaction device after degassing, and performing a polymerization reaction to obtain the ethylene-methacrylic acid-acrylate copolymer or the ethylene-acrylic acid-acrylate copolymer;
[0009] The reaction device is an autoclave, the polymerization reaction temperature is 85-95° C., the polymerization pressure is 23-27 MPa, the reaction time is 5-6 h, the initiator can be optionally an azo initiator, more preferably azobisisobutyronitrile, the acrylate is any one of methyl acrylate, ethyl acrylate, propyl acrylate or butyl acrylate; the concentration of the initiator in the mixture is 0.01-0.02 mol / L, and the mass percentage of the solvent (pure water and tert-butyl alcohol) in the mixture is 98-99%.
[0010] Furthermore, the polyamide resin is any one or more of PA66, PA610, PA612, PA1010, PA1012, PA1212, PA6, PA7, PA11 or PA12, and the viscosity of the polyamide resin is 100-170 mL / g.
[0011] Furthermore, the mass percentage of methacrylic acid or acrylic acid monomer in the ethylene-methacrylic acid-acrylate or ethylene-acrylic acid-acrylate is 2%-5%, such as 2%, 3%, 4%, 5%.
[0012] Furthermore, the glass fiber is a glass fiber made of at least one of E glass, H glass, R glass, S glass, D glass, C glass or quartz glass.
[0013] Furthermore, the stabilizer is one or more of an antioxidant, an ultraviolet absorber, and a hindered amine stabilizer.
[0014] Furthermore, the antioxidant is one or more of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol, β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, tris[2,4-di-tert-butylphenyl]phosphite or bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite.
[0015] Further, the ethylene-methacrylic acid-acrylate copolymer is any one of ethylene-methacrylic acid-butyl acrylate copolymer or ethylene-methacrylic acid-ethyl acrylate copolymer, and the ethylene-acrylic acid-acrylate copolymer is any one of ethylene-acrylic acid-butyl acrylate copolymer or ethylene-acrylic acid-ethyl acrylate copolymer, preferably ethylene-methacrylic acid-butyl acrylate copolymer.
[0016] Furthermore, the ultraviolet absorber is one or more of 2,2′-methylene-bis[4-tert-octyl-6-(2H-benzotriazolyl-2)]phenol and 2-(2′-hydroxy-5′-tert-octylphenyl)benzotriazole.
[0017] Furthermore, the hindered amine stabilizer is one or more of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine and N,N′-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,3-benzenediamide.
[0018] Furthermore, the lubricant may be one or more of carboxyl-terminated hyperbranched polyester, hydroxyl-terminated hyperbranched polyester, polyethylene wax, polyvinyl pyrrolidone or amino-terminated hyperbranched polyamide, preferably one or more of carboxyl-terminated hyperbranched polyester and amino-terminated hyperbranched polyamide.
[0019] The present invention also provides a method for preparing the polyamide composition, comprising the following steps:
[0020] S1: Weigh each component according to the ratio, and premix each component except glass fiber to obtain a premix;
[0021] S2: the premix of step S1 is put into an extruder for melt blending, glass fiber is fed in by side feeding, and extruded and granulated to obtain the polyamide composition.
[0022] The present invention also provides a method for preparing the polyamide composition. The screw length-diameter ratio of the twin-screw extruder is 36:1-48:1, the barrel temperature is 220-280°C, and the screw speed is 200-350rpm.
[0023] The invention also provides application of the polyamide composition in preparing electric tools, handles and elevator casters.
[0024] In summary, compared with the prior art, the present invention achieves the following technical effects:
[0025] (1) The polyamide composition provided by the present invention has high fluidity;
[0026] (2) The polyamide composition provided by the present invention has high tensile strength;
[0027] (3) The polyamide composition provided by the present invention has high adhesion to soft glue. DETAILED DESCRIPTION
[0028] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only embodiments of a part of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0029] Example
[0030] The present invention is further described below in conjunction with specific examples and comparative examples. The following specific examples are all preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the following examples, and are particularly not limited to the types of the various component raw materials used in the following specific examples.
[0031] 1. The sources of raw materials for the embodiments and comparative examples are as follows:
[0032] Polyamide #1: PA6, HY-2000A, viscosity 100mL / g, Haiyang Chemical Fiber;
[0033] Polyamide #2: PA66, U3600 NC01 SS, viscosity 140 mL / g, INVISTA, USA;
[0034] Polyamide #3: PA6, brand HY-2800A, viscosity 170mL / g, Haiyang Chemical Fiber;
[0035] Glass fiber: E glass fiber, ECS301HP-3-H, Chongqing International Composite Materials Co., Ltd.;
[0036] Ethylene-methacrylic acid-acrylate #1: Ethylene-methacrylic acid-butyl acrylate copolymer, methacrylic acid monomer content is 5%, homemade, prepared by the following method:
[0037] Ethylene, methacrylic acid and n-butyl acrylate are used as polymerization monomers for emulsion polymerization, wherein the mass percentages of ethylene, methacrylic acid and n-butyl acrylate in the polymerization monomers are 60%, 5% and 35% respectively; the specific preparation process is as follows: azobisisobutyronitrile (AIBN), pure water, tert-butyl alcohol (the mass ratio of pure water to tert-butyl alcohol is 5.3:1), methacrylic acid and n-butyl acrylate are placed in an autoclave and stirred evenly to obtain a mixture; the concentration of AIBN in the mixture is 0.01 mol / L, and the mass percentage of the solvent (pure water and tert-butyl alcohol) in the mixture is 98.4%; after degassing the reactor, ethylene is charged into it, and a polymerization reaction is carried out at a temperature of 80° C. and a pressure of 25 MPa, during which ethylene is continuously added and the pressure is kept constant, the polymerization reaction time is about 6 hours, and an emulsion with a solid content of 20% is obtained; the emulsion is purified and dried to obtain the ethylene-methacrylic acid-butyl acrylate copolymer;
[0038] Ethylene-methacrylic acid-acrylate #2: ethylene-methacrylic acid-butyl acrylate copolymer, the methacrylic acid monomer content is 2%, and the only difference from Preparation Example 1 is that the mass percentages of ethylene, methacrylic acid, and n-butyl acrylate in the polymerization monomers are 80%, 2%, and 18%, respectively. The types, amounts, and preparation process parameters of other materials are the same as those in Preparation Example 1 of ethylene-methacrylic acid-acrylate #1, and ethylene-methacrylic acid-butyl acrylate copolymer is obtained;
[0039] Ethylene-methacrylic acid-acrylate #3: ethylene-methacrylic acid-butyl acrylate copolymer, the methacrylic acid monomer content is 9%, the only difference from Preparation Example 1 is that the mass percentages of ethylene, methacrylic acid, and n-butyl acrylate in the polymerization monomers are 60%, 9%, and 31%, respectively, and the types, amounts, and preparation process parameters of other materials are the same as those in Preparation Example 1 of ethylene-methacrylic acid-acrylate #1, to obtain ethylene-methacrylic acid-butyl acrylate copolymer;
[0040] Ethylene-methacrylic acid-acrylate #4: ethylene-methacrylic acid-butyl acrylate copolymer, the methacrylic acid monomer content is 1%, and the only difference from Preparation Example 1 is that the mass percentages of ethylene, methacrylic acid, and n-butyl acrylate in the polymerization monomers are 80%, 1%, and 19%, respectively. The types, amounts, and preparation process parameters of other materials are the same as those in Preparation Example 1 of ethylene-methacrylic acid-acrylate #1, and ethylene-methacrylic acid-butyl acrylate copolymer is obtained;
[0041] Ethylene-methacrylic acid-acrylate #5: ethylene-methacrylic acid-butyl acrylate copolymer, the methacrylic acid monomer content is 11%, and the only difference from Preparation Example 1 is that the mass percentages of ethylene, methacrylic acid, and n-butyl acrylate in the polymerization monomers are 60%, 11%, and 29%, respectively. The types, amounts, and preparation process parameters of other materials are the same as those in Preparation Example 1 of ethylene-methacrylic acid-acrylate #1, and ethylene-methacrylic acid-butyl acrylate copolymer is obtained;
[0042] Ethylene-acrylic acid-acrylic acid ester #6: ethylene-acrylic acid-ethyl acrylate copolymer, the acrylic acid monomer content is 5%, the difference from Preparation Example 1 is that the mass percentages of ethylene, acrylic acid, and ethyl acrylate in the polymerized monomers are 60%, 5%, and 35%, respectively, and the types, amounts, and preparation process parameters of other materials are the same as those of Preparation Example 1 of ethylene-methacrylic acid-acrylic acid ester #1, to obtain ethylene-acrylic acid-ethyl acrylate copolymer;
[0043] Ethylene-methacrylic acid copolymer: The methacrylic acid monomer content is 5%. The difference from Preparation Example 1 is that the mass percentages of ethylene and methacrylic acid in the polymerized monomers are 95% and 5%, respectively. The types, amounts and preparation process parameters of other materials are the same as those in Preparation Example 1 of ethylene-methacrylic acid-acrylate, and ethylene-methacrylic acid copolymer is obtained.
[0044] Lubricant #1: carboxyl-terminated hyperbranched polyester, HYPER C101, Wuhan Hyperbranched Resin Technology Co., Ltd.;
[0045] Lubricant #2: hydroxyl-terminated hyperbranched polyester, HYPER H101, Wuhan Hyperbranched Resin Technology Co., Ltd.;
[0046] Lubricant #3: Polyethylene wax, A-C6A, Honeywell;
[0047] Lubricant #4: amino-terminated hyperbranched polyamide, HYER N101, Wuhan Hyperbranched Resin Technology Co., Ltd.;
[0048] Lubricant #5: Silicone lubricant, GT-300, Zhejiang Jiahua Fine Chemical;
[0049] Lubricant #6: Ethylene glycol monostearate, C34695, Anaiji Chemical;
[0050] Antioxidant; bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, REVONOX 608, the same substance was used in parallel experiments.
[0051] The preparation method of the polyamide composition of the embodiment and the comparative example of the present invention comprises the following steps:
[0052] S1: Weigh each component according to the ratio, and premix each component except glass fiber to obtain a premix;
[0053] S2: feeding the premix of step S1 into an extruder for melt blending, feeding glass fiber by side feeding, and extruding and granulating to obtain the polyamide composition;
[0054] Among them, the screw length-to-diameter ratio of the twin-screw extruder is 36:1-48:1, the barrel temperature is 220-280°C, and the screw speed is 200-350rpm; among them, the screw length-to-diameter ratio of the twin-screw extruder is 40:1, the barrel temperature is 270-250-250-250-250-250-260-280°C, and the screw speed is 200rpm.
[0055] 2. Various performance test methods
[0056] (1) Tensile strength: The tensile strength is tested according to the relevant standard of ISO 527-2-2012;
[0057] (2) Adhesion with soft glue: Use a homemade mold to firstly inject the reinforced nylon material to obtain a hard glue sheet, and then inject TPE soft glue on the nylon sheet. Use a tensile fixture to test the adhesion between nylon and soft glue;
[0058] (3) Spiral length: Use a homemade mold and injection molding under the same injection molding parameters to test the material flow length.
[0059] Table 1 Technical solutions and effects of the embodiments (in parts by weight)
[0060]
[0061]
[0062] Table 2 Comparative Examples Technical Scheme and Effects (Units are parts by weight)
[0063]
[0064] In Examples 1-10, polyamide resin, glass fiber, and ethylene-methacrylic acid-acrylate copolymer or ethylene-acrylic acid-acrylate copolymer are introduced at the same time. The obtained glass fiber reinforced polyamide compositions have high tensile strength and fluidity, and can have high adhesion with soft glue to keep the surface of the material smooth. Among them, the tensile strength is above 140 MPa, the spiral line length is above 400 mm, and the peeling force is above 500 N.
[0065] Comparative Examples 1-8 are all compared with Example 3. The mass percentage of methacrylic acid monomer in the ethylene-methacrylic acid-acrylate copolymer used in Comparative Example 1 is lower than 1.8%, which significantly reduces the adhesion between the polyamide composition and the soft glue; the mass percentage of methacrylic acid monomer in the ethylene-methacrylic acid-acrylate copolymer used in Comparative Example 2 is higher than 9.2%, which significantly deteriorates the tensile strength of the polyamide composition; too much ethylene-methacrylic acid-acrylate copolymer is added in Comparative Example 3, which deteriorates the fluidity of the system and significantly reduces the tensile strength of the composition; and no ethylene-methacrylic acid-acrylate copolymer is added in Comparative Example 4. Ester copolymer, unable to achieve the bonding performance of the polyamide composition and the soft glue; Comparative Example 5 did not add lubricant, so the bonding performance of the polyamide composition and the soft glue was reduced; the lubricant used in Comparative Example 6 was a silicone lubricant, which was easy to migrate to the surface of the material, reducing the contact between the material and TPE, thereby reducing the adhesion; Comparative Example 7 added ethylene-methacrylic acid copolymer, lacking the third comonomer, so that the acidic group reacted with nylon to cause degradation, reducing the material performance; the lubricant used in Comparative Example 8 was ethylene glycol monostearate, which had a relatively low melting point and was easy to agglomerate during the production process, resulting in changes in material components, and easy to migrate to the surface of the material to reduce the adhesion with TPE. None of the above comparative examples can simultaneously achieve high tensile strength, high fluidity, and achieve the effect of high adhesion between the polyamide composition and the soft glue.
[0066] Based on the test data of tensile strength, spiral length and peeling force with soft glue of the polyamide composition in Table 1 and Table 2, the polyamide composition prepared by Examples 1-10 has obvious advantages over the comparative example and can effectively meet the high standards of customers and the market.
[0067] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A polyamide composition, characterized in that By weight, it includes the following components: The mass percentage of methacrylic acid or acrylic acid monomer in the ethylene-methacrylic acid-acrylate or ethylene-acrylic acid-acrylate is 1.8%-9.2%; The lubricant is any one of hyperbranched polyester, hyperbranched polyamide or polyethylene lubricant.
2. The polyamide composition according to claim 1, characterized in that The polyamide resin is any one or more of PA66, PA610, PA612, PA1010, PA1012, PA1212, PA6, PA7, PA11 or PA12.
3. The polyamide composition according to claim 1, characterized in that The mass percentage of methacrylic acid or acrylic acid monomer in the ethylene-methacrylic acid-acrylate or ethylene-acrylic acid-acrylate is 2%-5%.
4. The polyamide composition according to claim 1, characterized in that The glass fiber is made of at least one of E glass, H glass, R glass, S glass, D glass, C glass or quartz glass.
5. The polyamide composition according to claim 1, characterized in that The stabilizer is one or more of an antioxidant, an ultraviolet absorber, and a hindered amine stabilizer.
6. The polyamide composition according to claim 5, characterized in that The antioxidant is one or more of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol, β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, tris[2,4-di-tert-butylphenyl]phosphite or bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite.
7. The polyamide composition according to claim 1, characterized in that The viscosity of the polyamide resin is 100-170 mL / g.
8. The polyamide composition according to claim 1, characterized in that The ethylene-methacrylic acid-acrylate copolymer is any one of ethylene-methacrylic acid-butyl acrylate copolymer and ethylene-methacrylic acid-ethyl acrylate copolymer, and the ethylene-acrylic acid-acrylate copolymer is any one of ethylene-acrylic acid-butyl acrylate copolymer and ethylene-acrylic acid-ethyl acrylate copolymer.
9. The method for preparing the polyamide composition according to any one of claims 1 to 8, characterized in that: The steps include: S1: Weigh each component according to the ratio, and premix each component except glass fiber to obtain a premix; S2: the premix of step S1 is put into an extruder for melt blending, glass fiber is fed into the extruder by side feeding, and the premix is extruded and granulated to obtain the polyamide composition.
10. Use of the polyamide composition according to any one of claims 1 to 8 in the preparation of electric tools, handles and elevator casters.
Citation Information
Patent Citations
High-surface low-wraping glass fiber reinforced PA composite material and preparation method thereof
CN106009655A
Nylon material well bonded with TPU (thermoplastic polyurethane) material and preparation method thereof
CN117402484A
Thermoplastic nylon moulding materials of toughness
GB1519355A
Polyamide moulding compositions
GB1575339A
Polyamide blends
US4246371A
Cited By
High-fluidity flat glass fiber reinforced PA6 composite material and preparation method thereof
CN122213667A